ChemInform Abstract: Enantio‐ and Diastereoselective Desymmetrization of α‐Alkyl‐α‐diazoesters by Dirhodium(II)‐Catalyzed Intramolecular C—H Insertion. Issue 43 (7th October 2016) - Miyazawa, Taku; Minami, Kazushi; Ito, Motoki; Anada, Masahiro; Matsunaga, Shigeki; Hashimoto, Shunichi
Abstract: The title reaction proceeds best in the presence of the Rh catalyst shown to form bicyclic ring systems with at least one cyclopentane unit in an enantio‐ and diastereoselective manner.